Geniposide plus chlorogenic acid reverses non-alcoholic steatohepatitis via regulation of gut microbiota and bile acid signaling in a mouse model in vivo - Li, Hongshan; Xi, Yingfei; Xin, Xin; Feng, Qin; Hu, Yiyang (Frontiers in Pharmacology, 2023)
Background: Geniposide and chlorogenic acid are the major active ingredients in Yinchenhao Decoction and are widely used as herbal medicines in Asia. This study further assessed their effects on improvement of nonalcoholic steatohepatitis (NASH) in a mouse model and explored the underlying molecular events in vivo. Methods: Male C57BL/6 and farnesoid X receptor knockout (FXR-/-) mice were used to establish the NASH model and were treated with or without geniposide, chlorogenic acid, obeticholic acid (OCA), and antibiotics for assessment of the serum and tissue levels of various biochemical parameters, bile acid, DNA sequencing of bacterial 16S amplicon, protein expression, and histology. Results: The data showed that the combination of geniposide and chlorogenic acid (GC) reduced the levels of blood and liver lipids, serum alanine aminotransferase (ALT), serum aspartate aminotransferase (AST), and the liver tissue index in NASH mice. In addition, GC treatment improved the intestinal microbial disorders in the NASH mice as well as the intestinal and serum bile acid metabolism. At the gene level, GC induced FXR signaling, i.e., increased the expression of FXR, small heterodimer partner (SHP), and bile salt export pump (BSEP) in liver tissues and fibroblast growth factor 15 (FGF15) expression in the ileal tissues of NASH mice. However, antibiotics (ampicillin, neomycin, vancomycin, and tinidazole) in drinking water (ADW) reversed the effect of GC on NASH and altered the gut microbiota in NASH mice in vivo. Furthermore, GC treatment failed to improve NASH in the FXR-/- mouse NASH model in vivo, indicating that the effectiveness of GC treatment might be through FXR signaling activation. Conclusions: GC was able to alleviate NASH by improving the gut microbiome and activating FXR signaling; its effect was better than each individual agent alone.